PENGARUH IMPLEMENTASI TRISILA TNI AL TERHADAP SEMANGAT PENGABDIAN PRAJURIT PANGKALAN TNI AL - Eko Arie Kurniawan; Sudardi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
Trisila TNI AL is a guidance for every naval soldiers as codes of conduct to perform in their office and their environment. The implementation of this codes of conduct is required to keep and enhance the spirit and dedication of the